Competent, trustworthy, and likeable? Exploring which peers influence photovoltaic adoption in Germany. (September 2022) - Scheller, Fabian; Graupner, Sören; Edwards, James; Weinand, Jann; Bruckner, Thomas
Abstract: Little is known about the role of active peer effects (interpersonal contact) compared to passive peer effects (noticing or seeing) regarding residential photovoltaic (PV) diffusion. Recent literature suggests that peer effects are determined by the perceived credibility of one's active peer connections regarding PV and passive peer effects. Utilising data from a survey of German house owners who either own a PV or indicate purchase intention (N = 1, 165), this paper explores the underlying mechanisms of active peer effects during different stages of PV adoption decision-making. Our findings suggest that the perceived credibility of peers on PV related issues is positively associated with the reported number of adopters in the decision-maker's peer group (passive peer effect) and also with the progress in the PV adoption decision process. Furthermore, we find a relationship between the perceived credibility of peers regarding PV and the reported influence strength of peer interactions throughout the decision-making processes of German householders, suggesting that subjective evaluations of peers play a role in active peer effects. Finally, we observe an association between the rate of self-initiated peer interactions about PV for respondents with a higher reported number of peers that have adopted PV, suggesting that passive effects (knowing peer PV adopters) play a role in initiating active peer interactions. These results are significant for all sub-groups, regardless of the decision progress. From a policy-making perspective, "bottom-up" efforts such as peer consultation and community-led outreach should be promoted in Germany to empower potential adopters. Highlights: Active peer effects are explored along the PV adoption decision-making process. Competency attribution of peers is directly influenced by PV peer adoption . Peer interaction influence is related to attribute perceptions in all decision stages. Number of PV peer adopters is associated with self-initiated peer contacts about PV. Contact rate by decision-makers is correlated with positive attributed peers.